Influence of melatonin supplementation on tissue response of endodontic sealers in Wistar rats - de Oliveira, Pedro Henrique Chaves [UNESP]; da Silva Rodrigues, Michael Júnio [UNESP]; da Silva, Cristiane Cantiga [UNESP]; de Barros Moraes Cardoso, Carolina [UNESP]; Faria, Flávio Duarte [UNESP]; Cosme-Silva, Leopoldo [UNESP]; Ervolino, Edilson [UNESP]; Gomes-Filho, João Eduardo [UNESP]; Sivieri-Araújo, Gustavo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (My University, 2025)
Objective: This study evaluated the influence of melatonin supplementation on tissue’s response of endodontic sealers in Wistar rats. Methodology: Forty-eight rats received subcutaneous implants of four polyethylene tubes: one empty (control) and three filled with endodontic sealers (AH Plus, Endofill and Sealapex). Half of the animals were supplemented with melatonin (ME) and the remaining treated with water (WA) for 15 days before the implantation until euthanasia, forming the groups: control-WA, AH Plus-WA, Endofill-WA, Sealapex-WA, Control-ME, AH Plus-ME, Endofill-ME and Sealapex-ME. After 5, 15 and 30 days, (n = 8) tubes were removed and evaluated in H&E., immunohistochemistry, PSR, VK and POL. The results were statistically analyzed (p < 0.05). Results: In animals treated with water, Endofill-WA evoked more intense inflammatory infiltrate compared to AH Plus-WA and Control-WA in a 30-day period (p < 0.05). In animals supplemented with melatonin, there was any difference among endodontic sealers' response in any period of analysis (p > 0.05). Comparing the individual response of each sealer, over a 30-day period, Endofill-ME and Sealapex-ME showed less inflammatory infiltrate compared to Endofill-WA and Sealapex-WA, respectively (p < 0.05). Immunostaining for IL-6 and TNF-α was less intense for all groups in animals supplemented with melatonin, in most periods, except for the Endofill sealer (p < 0.05). Furthermore, Endofill-ME at 5 days and AH-Plus-ME at 30 days showed a higher percentage of mature collagen fibers compared to the Endofill-WA and AH Plus-WA, respectively (p < 0.05). Positive structures for von Kossa staining and birefringent to polarized light were observed only for Sealapex-WA and Sealapex-ME in all periods. Conclusions: It can be concluded that melatonin influences the tissue response to endodontic sealers, modulating the inflammatory and reparative process.
Keywords: Endodontic sealers; Inflammation; Melatonin; Mineralization; Tissue response